(untitled) (Revista Direito em Debate, 2024)
This article proposes to debate the relevance of judicial actors as protagonists in the organization of society in emergency situations of public calamity. It seeks to provide an overview of the fundamental rights that can be accessed through the courts, and the relationship between the state and these rights, even in times of crisis. The study is based on a conversation with the Regional Prosecutor in Lajeado, a city located in the Taquari Valley in the state of Rio Grande do Sul, one of the many towns in the state affected by the floods that occurred in September 2023 and May 2024. From the data collected, it is possible to verify the need for extra-procedural action by such agents, showing that the needs of human beings go far beyond or, sometimes, are simply summarized in waiting for a hug that is not in the law.